2004
DOI: 10.1142/s0192415x04001783
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect ofGlycine tomentellaRoot Extract in Hamsters

Abstract: The influence of the aqueous crude extract of Glycine tomentella root (Leguminosae) on lipid metabolism was investigated in hyperlipidemic hamsters. It was found that the administration of the G. tomentella extract (GTE) leads to a decrease of high serum cholesterol and triglyceride levels induced by high-fat diet. The GTE also increased serum high-density lipoprotein (HDL) cholesterol and decreased serum low-density lipoprotein (LDL) cholesterol. The reduction of serum triglyceride levels was accompanied by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Phytochemical analysis shows the presence of polyphenols in the AGT (Ko et al, 2004). The concentration of polyphenols in AGT was 35.4 mg/g (Ko et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Phytochemical analysis shows the presence of polyphenols in the AGT (Ko et al, 2004). The concentration of polyphenols in AGT was 35.4 mg/g (Ko et al, 2004).…”
Section: Discussionmentioning
confidence: 92%
“…The root of Glycine tomentella Hayata (Fabaceae) has long been used in the Knimen area of Taiwan as an anti-inflammatory agent for the treatment of rheumatic illness (Ko et al, 2004), gout, arthritis, and body aches (Chen, 1979;Ko et al, 2004), indicative of its anti-inflammatory activity. Recently, herbal tea of glycine radix (GR) has been developed for commercial purposes in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been used to help treat arthritis and rheumatism for a long time (Ko, Wu, & Lin, 2004). Recently the herb has also been exploited as a functional tea, steeped wine and related products for commercial purposes in Taiwan, due to its health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the herb has also been exploited as a functional tea, steeped wine and related products for commercial purposes in Taiwan, due to its health benefits. It has been reported that the roots of G. tomentella Hayata has several biological activities, such as antioxidant (Chen & Pan, 2007;Chen, Shiao, & Pan, 2005), hypolipidaemic (Ko et al, 2004, Chen & Pan, 2007, analgesic (Lu et al, 2007), anti-inflammatory (Chen et al, 2005;Lu et al, 2007), and immunomodulatory (Chuang, Haugland, Pan, & Evensen, 2008).…”
Section: Introductionmentioning
confidence: 99%